Ultrasound-Targeted Microbubble Destruction Mediated si-CyclinD1 Inhibits the Development of Hepatocellular Carcinoma via Suppression of PI3K/AKT Signaling Pathway - Yan W; Cheng L; Zhang D (Cancer Management and Research, 2020)
Wei Yan,* Li Cheng,* Dongmei Zhang Department of Electrical Diagnosis, Changchun University of Traditional Chinese Medicine Affiliated Hospital, Changchun 130021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei YanDepartment of Electrical Diagnosis, Changchun University of Traditional Chinese Medicine Affiliated Hospital, Changchun 130021, People’s Republic of ChinaTel/Fax +86-0431-85380511Email Yanwei051719@163.comBackground and Aim: In our study, we aimed to investigate the effect of ultrasound-targeted microbubble destruction (UTMD)mediated si-CyclinD1 (CCND1) on the growth of hepatocellular carcinoma (HCC) cells.Patients and Methods: Bioinformatics analysis was performed to detect the difference of CCND1 expression of HCC and normal liver tissues. After treatment with UTMDmediated si-CCND1, the growth and apoptosis of HepG2 cells were detected by flow cytometry, MTT, EdU staining, colony formation assay, Hoechst 33,258 staining and Western blot analysis. The growth of HepG2 cells in vivo was also studied via xenograft tumor in nude mice.Results: CCND1 was highly expressed in HCC tissues and HCC cell lines. UTMDmediated si-CCND1 could inhibit the growth of HepG2 cells and promote apoptosis via suppression of the PI3K/AKT signaling pathway. UTMDmediated si-CCND1 could also suppress the growth of HepG2 cells in vivo.Conclusion: Our study provided evidence that UTMDmediated si-CCND1 could inhibit the growth of HepG2 cells and promote apoptosis via suppression of the PI3K/AKT signaling pathway.Keywords: hepatocellular carcinoma, ultrasound-targeted microbubble destruction, CCND1, PI3K/AKT signaling pathway